2002
DOI: 10.1007/s00203-002-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrate on oxalate- and glyoxylate-dependent growth and acetogenesis by Moorella thermoacetica

Abstract: Oxalate and glyoxylate supported growth and acetate synthesis by Moorella thermoacetica in the presence of nitrate under basal (without yeast extract) culture conditions. In oxalate cultures, acetate formation occurred concomitant with growth and nitrate was reduced in the stationary phase. Growth in the presence of [(14)C]bicarbonate or [(14)C]oxalate showed that CO(2) reduction to acetate and biomass or oxalate oxidation to CO(2) was not affected by nitrate. However, cells engaged in oxalate-dependent acetog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…We have shown that M. thermoacetica metabolizes oxalate very simply by a novel CoA-independent OFOR that catalyzes the oxidative decarboxylation of oxalate to 2 mol of CO 2 , coupled to the reduction of ferredoxin (or other electron acceptors). The apparent reaction is C 2 O 4 2Ϫ ϩ Fd ox 7 2 CO 2 ϩ Fd red i , 3 although we have not yet shown whether CO 2 or bicarbonate is the product that is released from OOR. Our results are consistent with previous studies, which indicate that incorporation of oxalate into cell material requires conversion to CO 2 (3,14).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…We have shown that M. thermoacetica metabolizes oxalate very simply by a novel CoA-independent OFOR that catalyzes the oxidative decarboxylation of oxalate to 2 mol of CO 2 , coupled to the reduction of ferredoxin (or other electron acceptors). The apparent reaction is C 2 O 4 2Ϫ ϩ Fd ox 7 2 CO 2 ϩ Fd red i , 3 although we have not yet shown whether CO 2 or bicarbonate is the product that is released from OOR. Our results are consistent with previous studies, which indicate that incorporation of oxalate into cell material requires conversion to CO 2 (3,14).…”
Section: Discussionmentioning
confidence: 74%
“…The apparent reaction is C 2 O 4 2Ϫ ϩ Fd ox 7 2 CO 2 ϩ Fd red i , 3 although we have not yet shown whether CO 2 or bicarbonate is the product that is released from OOR. Our results are consistent with previous studies, which indicate that incorporation of oxalate into cell material requires conversion to CO 2 (3,14). For example, M. thermoacetica can grow on oxalate even in CO 2 -free medium; however, when cells are grown on oxalate and CO 2 , very little radioactivity from 14 C-oxalate is incorporated into biomass (14).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations